Enlightening Faith Nurturing Strategies in Contextualization in Damarwulan Village - Gunarto, Rita Oktavia; Herman, Samuel (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research is motivated by the challenges of preserving and developing faith in Damarwulan Village, which boasts a rich and unique cultural and traditional heritage. Several issues have been identified, including nominalism, formalism in worship, and a lack of contextual approaches in faith preservation. The aim of this study is to explore effective strategies for nurturing the Christian faith, making it relevant to the local cultural and traditional context. The methodology employed is a case study with a qualitative approach, analyzing the process of faith revitalization through interviews and observations of the local congregation. The findings indicate that contextual renewal and preservation of faith can address the challenges of nominalism and formalism in worship, providing a solid foundation for deeper and more sustainable faith development. In conclusion, maintaining and growing faith that is aligned with the local cultural and traditional context is essential for strengthening the spiritual life of Christians in Damarwulan Village. This research also offers practical guidance for implementing faith-building strategies that are relevant to this specific context.